Efeito da incorporação de nitrato de cério nas propriedades físico-químicas e térmicas de resinas acrílicas termopolimerizadas - Campos, Débora e Silva (2019)
Introduction: The colonization of polymethyl methacrylate (PMMA) by microorganisms favors the development of prosthetic stomatitis. Cerium nitrate (CN) has been shown to be effective antifungal when incorporated into PMMA, however, physical-chemical and thermal properties were not analyzed.Objective: To evaluate the effects of the incorporation of cerium nitrate in thermopolymerized PMMA by microwave energy in physicochemical and thermal properties. Materials and Methods: A total of 130 disks (10x5mm) were made in thermally activated PMMA. Five groups (n = 26) were obtained: two control groups (GC1-PMMA and GC2-PMMA + alcohol) and three experimental groups containing different percentages of cerium nitride (NC-0.25%, NC-0.5% and NC-1%). Surface analysis was evaluated by Scanning Electron Microscopy and surface roughness. The color was checked by spectrophotometry and the color difference having GC1-PMMA as the reference. X-Ray Fluorescence analyzed the chemical composition of the samples. Thermal analysis of thermogravimetry and differential scanning calorimetry verified, respectively, the mass loss and the heat flow, including the glass transition temperature. Results: The NC-1% group presented significantly higher surface roughness, reaching a value for Sa (0.222μm) slightly above the limit of clinical relevance (0.2μm). The color variations presented by the groups relative to GC1-PMMA were clinically acceptable. X-ray fluorescence detected the presence of cerium in the experimental samples. The mass loss of PMMA was not significantly altered with the addition of alcohol and / or cerium nitrate. The characteristic curves of the differential scanning calorimetry confirm the presence of cerium nitrate in the experimental groups and show that the glass transition temperature of the PMMA did not show great modifications. Conclusion: The groups NC-0.25% and NC-0.5% presented better results in the surface analysis, being a promising alternative for the prevention of prosthetic stomatitis.